STUDI POTENSI PAD DARI RETRIBUSI PARKIR FASILITAS LAYANAN RUMAH SAKIT UMUM DI KOTA PALU (STUDI KAJIAN RUMAH SAKIT: UNDATA, BK DAN BUDI AGUNG) - Jurair, Jurair (MEKTEK, 2005)
One of the PAD potential, which has not been deeply observed is retribution collection of parking area, whether on the road parking or on the parking area. The result of this study is showing that there is a promising potebtial from parking area of three of hospital observed as source of income if assumed that park is a time required by vehicle to enter and exit a long of 5 minutes, the income captured from these three hospital park areas will be around of Rp. 1,025,500,-/day or Rp. 369,180,000,-/year. But, if assumed that park is a time required by a vehicle of about 10 minutes to enter and exit, then the income resulted will be Rp. 971,000,-/day or Rp. 349,560,000,-/year